Field reports form for submitting seasonal observations of Iowa birds, Tom Johnson, spring 1998 - Johnson, Thomas N.et al (1998)
An annotated list of birds sighted by Tom Johnson and three others. Includes maps of birding sites. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed/flatbed